Temporal and spatial variability in 'Tetracotyle' type and metacercariae infection in the South African sardine, Sardinops sagax - Weston, Laura Frances (Department of Biological Sciences, 2014)
Spatial and temporal variation of "tetracotyle" type metacercariae infection in the eyes of the South African sardine, Sardinops sagax, was examined to elucidate the potential use of this parasite as a biological tag, and to test the hypothesis that the sardine population is divided into discrete western and southern subpopulations or stocks. Adult S. sagax specimens of 15 to 22 cm caudal length were collected monthly from five commercial fishery landing harbours to the west (St. Helena and Gans Bay) and to the east (Mossel Bay and Port Elizabeth) of Cape Agulhas in 2011 and 2012. Samples were preserved whole in 70% ethanol, or frozen, and then bagged and labelled. Fish were measured (caudal length in cm), sexed and dissected and summary statistics on the infection by "tetracotyl"e- type metacercariae in their eyes were recorded. Prevalence of infection (%), infection intensity and parasite abundance were analysed seasonally, over a period of 18 months, in fish caught to the west of Cape Agulhas and presumed to be part of the putative western stock of sardine, and in fish caught to the east of Cape Agulhas presumed to be part of the putative southern stock. Generalised linear models were used to model these three indices as dependent on stock, season, year and caudal length, where a binomial distribution was assumed for prevalence and a negative binomial distribution was assumed for infection intensity and parasite abundance. All factors contributed significantly to all models, but it was found that stock was the most significant contributor to the deviance seen in prevalence (%) and parasite abundance, and was the second most important contributor to the deviance seen in infection intensity. Fish to the west of Cape Agulhas were found to have significantly higher parasite loads in comparison to fish from the east of Cape Agulhas (p< 0.001). Season was the second most significant contributor to the deviance seen in prevalence and abundance, and was the most important contributor to the deviance seen in infection intensity, indicating that a seasonal signal was present. This seasonal signal was slightly delayed in fish from the putative southern stock in comparison to those from the putative western stock. Interannual differences in infection rates were also observed, being higher in 2012 compared to 2011. These results suggest that """"tetracotyle- type metacercariae can be used as a biological tag in stock discrimination studies and that, despite temporal variability, the clear spatial difference in the distribution of infection of S. sagax by """"tetracotyle- type metacercariae supports the hypothesis of western and southern stocks of sardine off the coast of South Africa.